(untitled) (Indian Journal of Arid Horticulture, 2013)
The study was carried out on twenty genotypes of bottle gourd collected from diversified areas of the country assessed under rainfed condition for genetic variability, heritability and genetic advance in respect of 16 quantitative characters. The genotype LS-6 recorded the highest fruit yield per plant, highest no of fruits per plant lowest sex ratio and highest fruit set percent, followed by LS-20. The phenotypic and genotypic coefficient of variation for different characters ranged from 6.270-34.045 and 3.749-30.732 respectively. The highest PCV and GCV were observed for fruit yield per plant, fruit length, no. of fruits per plant and sex ratio indicating the extent of variability based in these characters. High heritabilty coupled with higher genetic gain was observed for no. of seed per fruit, fruit length, no. of fruits per plant and yield per plant indicating the additive gene action. Days to first fruit harvest showed moderate to low heritability with low genetic gain expressed non -additive gene action governing these characters.